A new medium in art: Origins, hypotheses, theories and discourses - Ortuño Mengual, Pedro (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
The video was considered by Gene Youngblood (1979) as a new medium of artistic creation, whose codes will open new perspectives to the moving image giving it its own aesthetic entity. Various theories related to communication and art by authors such as Wiener, Benjamin, Brecht, McLuhan, Burris are analyzed. Likewise, he studies pioneering works and the use of the feedback loop as a element between the emitter and the receiver. Wipe Cycle (1969) by Frank Gillette and Ira Schneider and Time Delay Room (1974) by Dan Graham will show us the keys to understanding the inner workings of a new medium that had just been born.